Pathological Bites Complicated by Parafunction of the Masticatory Muscles - Khasanovich, Aliev Navruz (American Journal of Biology and Natural Sciences, 2024)
Treatment of patients with the syndrome of pain dysfunction of the temporomandibular joint remains one of the most difficult and urgent problems of modern dentistry; treatment with an occlusive splint, restoration of normal occlusion does not always lead to normalization of the position of the articular disc. According to the authors, in addition to dental treatment, medication therapy, physiotherapy, and psychotherapy are also necessary.